Commercial thinning and its potential for contribution to the timber supply in British Columbia’s Interior forests : a look at Finnish and Swedish forest practices and their applicability in British Columbia’s Interior forests - Christian, David (SLU/Southern Swedish Forest Research Centre, 2014)
Thinning is the partial removal of trees in a forest stand prior to final harvest. The term can be divided in pre-commercial thinning where little if any volume is removed from the stand and commercial thinning where removals are intended to provide a positive economic result. From a silvicultural point of view, the goal of thinning is to enhance future crop tree quality by removing low-quality stems and providing sufficient space for the accelerated development of retained ones (Huuskonen & Hynynen, 2006).